Popliteal Artery Injury After Fracture and/or Dislocation of the Knee: Risk Stratification for Revascularization Outcome. (March 2022) - Hsieh, Yun-Huan; Lee, Min-Chao; Hsu, Chung-Chen; Chen, Shih-Heng; Lin, Yu-Te; Lin, Chih-Hung; Lin, Cheng-Hung
Abstract : Background: Managing complex knee trauma involving both vascular and osseous injuries is challenging, yet the available guidelines for efficient popliteal artery injury management after high-velocity blunt knee trauma remain conflicting and inconsistent. In this study, the authors aim to identify the risk factors associated with delayed limb amputation and ischemic muscular sequela postrevascularization. Furthermore, we propose a treatment algorithm to improve the limb salvage rate. Methods: Patients who presented with traumatic popliteal artery injury resulting in vessel occlusion or rupture, followed by fracture and/or dislocation of the knee from January 2008 to December 2013, were included for retrospective review. Results: Overall delayed amputation rate was 24% (7/29) and 16% (4/25) after successful revascularization. Mangled Extremity Severity Score is higher in the delayed amputation group than the limb-salvaged group ( P = 0.02). Higher-impact force ( P = 0.03), ischemic limb on presentation ( P = 0.03), prolonged ischemia time ( P = 0.04), unstable hemodynamics ( P = 0.01), longer operation time ( P = 0.04), and prolonged intensive care unit stay ( P = 0.03) are risk factors of delayed amputation. Longer ischemia time ( P = 0.04) and length of popliteal artery injury ( P = 0.02) are associated with ischemic muscular sequela. Conclusions: Mangled Extremity Severity Score is a reliable predictor of limb salvage. An algorithmic approach may improve the outcome of popliteal artery injury after high-velocity blunt knee trauma.